Subjective quality of life and schizophrenia: results from a large cohort study based in Chinese primary care - Christine Migliorini; Carol Harvey; Cailan Hou; Shibin Wang; Fei Wang; Zhuo-Hui Huang (BMC Psychiatry, 2024)
Abstract Introduction Much confusion exists between health-related QoL (HRQoL) scales and subjective QoL (SQoL) scales. One method to avoid confusion is use of a single question that asks What is your quality of life? or similar. This study explored the relationship between biopsychosocial factors and high SQoL, SQoL stability, and factors associated with improving SQoL. Method We conducted a large cohort study of community-dwelling Chinese adults with schizophrenia, with two data points (2015–2016 (N = 742), 2017–2018 (N = 491)). Demographic and clinically related items and a comprehensive suite of published measures were collected. Direct logistic regressions were used to explore links between biopsychosocial factors and high SQoL and Improvement in SQoL across time. Results Sample at Baseline: Male = 62.3%; Med age = 38.5 years; Med Age at illness onset = 24 years; SQoL Mode = neither poor nor good. Three independent variables predicted high SQoL at T1. Contemporary age and the presence of clinically relevant symptoms had a negative relationship with high SQoL; insight had a positive relationship with high SQoL. SQoL changed significantly across time with a modest effect size. Age at illness onset was the single independent variable linked to improving SQoL favoring being older at the time of illness onset. Discussion/Conclusions SQoL can be high and changeable. While symptomology and illness insight may affect SQoL self-appraisals at single points in time, only age of illness onset was connected with improving SQoL. Thus, public health measures to delay illness onset are important. In addition, care about the distinction between HRQoL and SQoL in study design and choice of measures is necessary and will depend on the purpose and context.